C677T methylenetetrahydrofolate reductase polymorphism, folate and homocysteine levels and the risk of colorectal cancer (Annals of Medical Research, 2021)
Aim: Colorectal cancers are common in the world and many factors play a role. MTHFR (methylenetetrahydrofolate reductase) gene polymorphisms cause a predisposition to cancer formation. C677T polymorphism is the most common among these. To evaluate the role of MTHFR polymorphisms in colorectal carcinogenesis, we examined the associations between MTHFR mutations, homocysteine levels, plasma folate levels and colorectal cancer risk.Materials and Methods: During two years period, 101 naive colorectal cancer cases and 95 controls were enrolled to the study and groups were matched for age, sex and smoking. The presence of the mutation was determined by real-time PCR amplification of genomic DNA using Light.Results: Although only 1 of the cancer patients was homozygous mutant Val/Val, this mutation was present in 10.5% of the control group and this difference was statistically significant (p